Pressure-dependent dielectric properties in a polyurethane elastomer - Hwang, Seung Won; Shin, Jae Sup; Shin, Min Jae; Kim, Chy Hyung (Journal of the Korean Physical Society, 2017)
The dielectric responses of polyurethane films were investigated in the pressure range from atmospheric to 20 kpsi and in the frequency range from 0.05 Hz to 4 KHz at −50, 0, 29, 50, and 80 ◦ C, where T g is close to −15 ◦ C (α-relaxation) and where the glass temperature of the chain extender is about 80 ◦ C (I-relaxation). When a higher pressure was applied to the material, a lower dielectric constant (k’ ) was obtained owing to the suppression of polarization motions by the external pressure. However, k’ increased with rising pressure at temperatures above 50 ◦ C and at high frequencies due to the predominant thermal effect expanding the film outwards, where a dispersive α-relaxation occurred. Both α- and I-relaxations followed the pressure-frequency superposition principle with a different shifting factor, a ( p ), where the α-relaxation showed a faster migration of the relaxation time with changing pressure and a ( p ) values larger than those of I-relaxation. The two relaxations observed at 29 ◦ C demonstrated linear relations between 1/k’ and pressure and between ln a ( p ) and pressure, regardless of the film thickness.